Assessment of metal pollution in soil and social impact towards community at Jeli, Kelantan - Ismail, Fatin Hanani (2018)
The soil at rubber plantation at Jeli District potentially pollute by anthropogenic activity of this agriculture. This study was aimed to determine the concentration of metal in soil samples, to assess the metal pollution in soil samples and to determine the social impact of rubber plantation towards community. The soil samples were collected at two stations with the two points for each station and two times during dry and wet season. The total concentrations of selected metals were analysed using X-ray ﬂuorescence (XRF). The metal pollution assessment including enrichment factor (EF), geoaccumulation index (I-Geo), contamination factor (CF) and pollution load index (PLI) has been applied to assess the metal contamination in the soil. Questionnaire has been used to detennine the social impact of rubber cultivation. The descriptive analysis was employed to analyse the data. In dry season the mean concentration of studied metals follow the decreasing concentration in the order of Si (667500.00 mg/kg) > Al (203000.00 mg/kg) > K (16825.00 mg/kg) > Ti (13120.00 mg/kg) > Zr (4777.5O mg/kg) > Ca (2012.50 mg/kg) > Mn (505.75 mg/kg) > Cl (494.00 mg/kg) > Cr (341.25 mg/kg) > Zn (190.25 mg/kg) > Sn (161.00 mg/kg) > Pb (149.00 mg/kg). During wet season the mean concentration of studied metals follow the decreased order of Si (755750.00 mg/kg) > Al (146000.00 mg/kg) > K (l2095.00 mg/kg) > Ti (9562.50 mg/kg) > Zr (6505.00 mg/kg) > Ca (19l5.00 mg/kg) > Cl (1274.25 mg/kg) > Mn (437.50 mg/kg) > Cr (279.00 mg/kg) > Sn (186.25 mg/kg) > Pb (152.75 mg/kg) > Zn (150.25 mg/kg). The result from pollution assessment shows the studied area was unpolluted by the metals since the PLI value for all station less than l. The outcome ﬁom social impact study reveals the owner of the rubber cultivation and rubber tappers have a positive perception towards rubber sector as economic source. In aspect of attitude, majority of respondents realize that protecting the enviromnent is our responsibility. The value of metal concentration can be useful as a database for the environmental monitoring. While, the assessment of social impact towards community is important in identifying and distinguishing impacts from the rubber plantation.